Água como tema central para uma aprendizagem significativa de conceitos de química na perspectiva da alfabetização científica - Santos, Valeria Marinho Paes Dos [UNIFESP] (2020)
Science Teaching, such as Chemistry, Physics and Biology, as well as Mathematics, are constant challenges to teaching, mainly for the construction of scientific knowledge and related concepts. It is observed that the most of students have basic conceptual errors until the end of high school, and researchers such as Pozo and Crespo, Cachapuz and Delizoicov, Chassot, Sasseron and Carvalho both point out the existence of difficulties in understanding at different levels of education, up to even among professors in the field, but also highlight the need to renew Science Education beyond memorization, defending the importance of Science Education from the perspective of scientific literacy, which promotes the formation of active and critical subjects, capable of transforming society indeed. In addition to these, Marcondes and Mortimer still emphasize the importance of approaching Science Teaching through contextualized thematic units, accompanied by diversified activities that favour the active and critical participation of the main subject of learning: the student. Such challenges led to the development of this research, having “Water” as the guiding theme of the teaching-learning process of the concepts of Chemistry, as chemical element, atom, molecule, concentration, among many others, given the wealth of possibilities and context for your approach. Qualitative and in a "covert" research format, approved by the Ethics and Research Committee, this work was supported by Ausubel's theory of Meaningful Learning. It was found that the diversified activities, complementary to the proposals of the current curriculum, elaborated and carried out based on Bardin's methodology and content analysis, contributed to facilitate the understanding, construction and development of knowledge related to chemical concepts in a significant way, substantially implying in the reflection on pedagogical practices. Anchored in the students' previous knowledge, and considering them as protagonists in the teaching-learning process, the diagnostic activity made it possible to survey these “subsumers”, becoming the basis for the elaboration of data collection and analysis instruments, as well as for the elaboration of complementary diversified activities, enabling the construction of new concepts and the reframing, adaptation and improvement of existing ones. During the process it was possible to verify the students' development, regarding the ability of written and spoken expression, interpreting the concepts of chemistry with the other areas of knowledge in a critical way. The results showed a significant improvement in learning, indicated by the analysis of the categories from the investigation of the texts, contributing to the teaching of chemical concepts from the water theme, in a perspective of scientific literacy. It is intended that this research can contribute to expand future work on the topic, in order to the concepts related to Chemistry are built with a view to meaningful learning and respective scientific literacy for the formation of the critical and active citizen in the society in which he lives.